(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Salivary stone disease (SSD), also known as sialolithiasis, represents one of the most prevalent pathologies of the salivary glands, accounting for up to half of all disorders affecting this anatomical region. Despite the availability of diagnostic criteria and characteristic clinical manifestations, the rate of diagnostic errors remains unacceptably high, often resulting in delayed or inadequate treatment and an increased risk of chronic inflammation and complications. Current therapeutic strategies are predominantly focused on surgical management and resolution of acute inflammatory episodes, while insufficient attention is paid to early diagnosis, prognostic assessment, and prevention of recurrence. The present study aimed to identify unresolved issues and define prospective research directions in predicting the development, clinical progression, and outcomes of salivary stone disease. The analysis revealed the absence of a rational experimental model of SSD, as well as the lack of a scientifically validated system of prognostic tests suitable for both inpatient and outpatient settings.